This is not a firedrill : crisis intervention and prevention on college campuses - Myer, Rick.; James, Richard K., 1942-; Moulton, Patrice; Wiley InterScience (Online service) (Hoboken, N.J. : Wiley ; Chichester : John Wiley [distributor], 2010)
Practical Information and Tools to Create and Implement a Comprehensive College Campus Crisis Management ProgramWritten by three seasoned crisis intervention/prevention specialists with over fifty years combined experience in the field, This is NOT a Fire Drill: Crisis Intervention and Prevention on College Campuses is a practical guide to creating a comprehensive college campus crisis management program. Authors Rick Myer, Richard James, and Patrice Moulton provide university administrators, faculty, and staff with invaluable hands-on examples, general tactics, and strategies along with specif.
Front Matter -- Or a Tornado or Earthquake Drill -- Boilerplate: The Basics of Crisis Intervention -- Herding Cats: Organizing a Crisis Response -- Duller Than Dirt ; More Valuable Than Gold: Policies and Procedures -- The Best of Times and the Worst of Times: The Tale of Two Laws -- Reality Check: Entry into the System -- What You See Is What You Get or Maybe Not: Assessment of the System -- No Rest for the Weary: System Recovery After a Crisis -- Not Buying a Pig in a Poke -- Basic Training -- One Day at a Time: Survivorship in the Aftermath -- Leadership Checklist: Preparing Your Campus for Crisis -- Author Index -- Subject Index.
Includes indexes.
Includes bibliographical references and indexes.
Print version record.
Keywords: School crisis management; Universities and colleges -- Security measures; Universities and colleges -- Safety measures; Crisis intervention (Mental health services) -- United States; Crisis management -- United States; Traumatic shock; Universities and colleges -- United States -- Administration; Education; Electronic books